Determinants of Early Radiographic Progression in Ankylosing Spondylitis - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2010)
Objective. To investigate the demographic and clinical characteristics associated with early, extensive radiographic changes in ankylosing spondylitis (AS). Methods. Radiographic severity was assessed cross-sectionally in 235 patients with AS using the Bath AS Radiological Index spine score (BASRI-s). Patients with extensive radiographic changes on the lumbar portion of BASRI-s were defined as the early axial ankylosis (EAA) Group. ANCOVA and logistic regression analyses were used to identify factors affecting EAA. Results. Most study patients were men (139/235, 59.0%). Mean disease duration was 12.4 +/- 9.3 years. Fifteen percent of women and 34.8% of men with AS were in the EAA group. HLA-B27-positive men with AS had significantly higher BASRI-lumbar scores, while HLA-B27 had no effect on radiographic progression of axial disease in women with AS. Peripheral joint involvement was associated with slow radiographic progression. Hip involvement had no effect on axial progression but uveitis was more frequent in the male EAA group. The odds for an HLA-B27-positive male patient with AS who did not have peripheral arthritis of having a BASRI-lumbar score of 3 or higher were 3.4 (77% chance to have axially progressive disease). Presence of uveitis increased these odds to 93%. Only 15% of female patients with AS had EAA, and the absence of peripheral arthritis was the only clinical measure associated with EAA in this group. Conclusion. EAA was more frequent in men with AS than in women. Absence of peripheral arthritis, HLA-B27 positivity, and uveitis were associated with multiple syndesmophytes or fusion of multiple vertebrae of the lumbar vertebrae. (First Release Sept 15 2010; J Rheumatol 2010;37:2356-61; doi:10.3899/jrheum.100094)
Keywords: ANKYLOSING SPONDYLITIS; RADIOGRAPHIC PROGRESSION; GENDER; SEVERITY; CLINICAL-FEATURES; DISEASE EXPRESSION; RADIOLOGY INDEX; SEVERITY; HLA-B27; ASSOCIATION; ONSET